A model of international roaming regulation and competition in European mobile markets - Edmond Baranes; Cuong Hung Vuong (International Telecommunications Society (ITS), 2021)
This paper investigates the impacts of the current roaming rules on domestic competition and welfare. We consider a model for two countries in which each country has two operators that compete in the retail market for access services and also in the wholesale market for roaming. We first derive equilibrium prices in the two markets when operators are not subjected to regulatory restrictions. We then introduce Roaming Like At Home (RLAH) obligation and show how retail tariffs and wholesale roaming charges can be sensitive to this regulatory regime. Since introducing a fair use clause in roaming regulation can be a tool to avoid permanent roaming, we study different cases depending on whether RLAH is acompagnied by a fair use safeguard or not. We emphazise the most interesting results, considering the role played by cost and demand asymmetries between operators and countries.
Keywords: L13; L51; L96; 330; International roaming; mobile telecommunications; roaming like at home; fair use policy; interconnection